Polymerisable surfactants for polymethacrylates using catalytic chain transfer polymerisation (CCTP) combined with sulfur free-RAFT in emulsion polymerisation. (15th February 2020) - Shegiwal, Ataulla; Wemyss, Alan M.; Liarou, Evelina; Town, James; Patias, Geogios; Atkins, Christophe J.; Marathianos, Arkadios; Lester, Daniel W.; Efstathiou, Spyridon; Haddleton, David M.
Graphical abstract: Highlights: Statistical copolymers of methacrylic acid and methyl methacrylate were synthesised via free radical catalytic chain transfer polymerisation (CCTP) in emulsion to form a hydrophilic emulsifier/surfactant. The vinyl-terminated oligomers were in turn utilised as chain transfer agents, with no further purification, for the formation of diblock copolymers with butyl and methyl methacrylate which constitutes the emulsifier via sulfur-free reversible addition–fragmentation chain transfer polymerisation (SF-RAFT). These polymers were solubilized with various concentrations of ammonium hydroxide and utilised in the surfactant-free emulsion polymerization of butyl methacrylate using persulfate initiators, which also stabilized the polymer particles with observed no coagulation, with solid contents as high as 40%. Abstract: Statistical copolymers of methacrylic acid and methyl methacrylate were synthesised via free radical catalytic chain transfer polymerisation (CCTP) in emulsion to form a hydrophilic emulsifier/surfactant. The vinyl-terminated oligomers were in turn utilised as chain transfer agents, with no further purification, for the formation of diblock copolymers with butyl and methyl methacrylate which constitutes the emulsifier via sulfur-free reversible addition–fragmentation chain transfer polymerisation (SF-RAFT). In turn these polymers were solubilized with various concentrations of ammonium hydroxide and utilised in the surfactant-free emulsion polymerization of butyl methacrylate using persulfate initiators, which also stabilized the polymer particles with observed no coagulation, with solid contents as high as 40%.